(untitled) (Progressive Agriculture, 2020)
A study was done for soil characterization and soil fertility assessment in Char Latif and Char Monpura of Bhola District to identify suitable crops for increasing cropping intensity and crop yields. The soils of Char Latif were almost silt loam to silty clay loam in texture. Soil pH values were slightly alkaline in reaction. The organic matter contents were low to medium (1.23-2.53%), the total N very low to low (0.08-0.22%), available P low to very low (4.67-14.1µg g-1 soil), available S low to very high (4.02-156.8 µg g-1 soil) and exchangeable K low to optimum (0.138-0.311%), exchangeable Ca and Na very high in Char Latif areas. At Char Monpura areas, the soils were silt loam to silty clay loam in texture. The soil pH was neutral to slightly alkaline in reaction. The organic matter contents of the soil were low to medium (0.21-2.60%) and the total N contents were very low to low (0.03-0.18%). Available P contents were very low (2.40-6.65 µg g-1 soil). Available S contents were low to very high (4.02-156.8 µg g-1 soil). Exchangeable K, Ca and Na contents were medium to optimum (0.20-0.48 me%), in desired level (4.54-9.07me%) and very high level (1.64-5.14me%), respectively. The soils of both char land areas were normally erosive having low fertility and low water holding capacity. Generally, farmers of char lands cultivated local varieties of crops. As a result, crop yields are low. High yielding profitable crops and crop cultivation measures could be recommended for both of the Char Latif and Char Monpura areas. The findings could help the government and the other organizations to take proper steps for improving livelihood of the char peoples by improved crop varieties and management practices. Hence, there is great opportunity to increase crop production through intensification of crop cultivation with the selection of appropriate crop varieties and soil management at char lands. Progressive Agriculture 31 (1): 56-67, 2020